Problem-based learning: undergraduate Thai nursing students' perceptions. - Arpanantikul, Manee; Luecha, Yuwadee (Pacific Rim International Journal of Nursing Research)
Problem-based learning, a self-directed means of learning, has been implemented, throughout the world, as a teaching method in nursing. Although schools in Thailand have adopted problem-based learning as a primary teaching-learning method, little is known about how Thai nursing students feel about using such a self-directed approach. Thus, this qualitative study sought to explore undergraduate Thai nursing students' perceptions, regarding learning through the use of problem-based learning, after taking their first 16 week self-directed learning nursing course. A total of 147 first-year nursing students responded to an open-ended question regarding their perceptions about problem-based learning. Data revealed, via content analysis, students had both optimistic and pessimistic perceptions regarding problem-based learning. Optimistic perceptions were found to include: being an active learner; being a systematic learner; developing friendly relationships; adjusting personal characteristics when learning; and, having freedom while learning. Pessimistic perceptions were found to consist of: being unexcited about learning; carrying out time-consuming learning activities; and, obtaining limited knowledge. These findings provide, for the first time, an understanding of the perceptions of undergraduate Thai nursing students regarding problem-based learning.